A Comprehensive Review of AI's Impact on Healthcare: Revolutionizing Diagnostics and Patient Care - Mohammad Ali (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Patient care, diagnosis, and treatment could all be revolutionized by the use of artificial intelligence (AI) in healthcare. This essay investigates the broad implications of AI in healthcare across several fields. It starts out by highlighting the crucial role that AI plays in medical imaging and showing how AI-powered algorithms improve diagnostic precision and speed up picture interpretation. Personalized medicine is then discussed, with examples of how AI-driven insights enable customized treatment strategies based on unique patient data. As the paper explores the complicated ethical environment of AI-enhanced diagnosis and care, ethical questions take center stage. The conversation covers patient autonomy, algorithmic bias, data privacy, and responsibility, illuminating the difficulties and solutions to appropriately address these issues. The report also includes case studies of how AI has been successfully applied in healthcare contexts. These real-world examples demonstrate AI's benefits for radiology, oncology, remote monitoring, drug discovery, and more, demonstrating the technologies' disruptive potential. The report also looks ahead to AI's potential contributions to medical care. The applications of AI are positioned to transform the healthcare industry, from tailored treatment pathways to cutting-edge medical imaging and predictive healthcare. It focuses on how AI technologies and healthcare professionals work together to improve diagnoses, supplement clinical decision-making, and empower patients through remote monitoring and participation. But there are difficulties in incorporating AI into therapeutic practice. The study outlines the challenges and constraints, including the necessity for human-AI cooperation, algorithm validation requirements, and data quality issues. To the fullest extent possible, AI's potential in healthcare must be overcome. The ramifications of AI for healthcare personnel are highlighted in the paper's conclusion, along with the significance of upskilling to successfully negotiate the rapidly changing healthcare sector. In essence, this article thoroughly examines the dynamic interaction between artificial intelligence (AI) and healthcare, providing insights into the current situation, difficulties, possibilities, and the trajectory of AI in patient care going forward. The promise of improved patient outcomes, improved diagnoses, and a more effective and patient-centered healthcare environment underscores the importance of AI in healthcare even as it continues to develop.